HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL TIK-TOK DENGAN BODY IMAGE PADA GENERASI Z - Reflin Natalia Radjaki; Wahyuni Kristinawati (Bajang Institute, 2024)
Body image is an individual's mental image and subjective views that can affect the sense of satisfaction and dissatisfaction with oneself which is influenced by several factors, one of the factors that affect body image is the intensity of using tik-tok social media. This study aims to determine the relationship between the intensity of use of tik-tok social media that focuses on content with body image in generation Z. He data collection method was carried out online via google form and distributed via whatsapp and telegram. The sample taken amounted to 206 using incidental sampling technique. The results found that the intensity of using tik-tok social media with fashion, a day in my life and dance content has a very significant positive relationship with body image in generation Z, with r = 0.601 and sig value = 0.000 (p>0.05). Which means that the hypothesis in this study is accepted